2009
DOI: 10.1007/s11113-009-9136-7
|View full text |Cite
|
Sign up to set email alerts
|

The Post-Communist Fertility Puzzle

Abstract: Fertility has unanimously declined across the entire post-communist region. This study explores the variation in fertility trends over time among these countries and assesses to what degree three explanations are applicable: second demographic transition (SDT), postponement transition (PPT) or reaction to the economic crisis. Moreover, on the basis of SDT and PPT theoretical tenets, as well as descriptive evidence, the economic context is hypothesized to be linked to two processes of fertility decline converse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 44 publications
2
82
0
10
Order By: Relevance
“…However comparing Kaplan-Meier failure curves during the different periods reveals that the difference in second birth transitions between the two post socialist periods was largely driven by postponement of the second birth. This finding is in alignment with research that found a higher likelihood of postponement in more favorable economic contexts (Billingsley 2010). Still, the main picture is that of a decline in second birth rates after 1990 and that rates did not increase again to their pretransition levels.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However comparing Kaplan-Meier failure curves during the different periods reveals that the difference in second birth transitions between the two post socialist periods was largely driven by postponement of the second birth. This finding is in alignment with research that found a higher likelihood of postponement in more favorable economic contexts (Billingsley 2010). Still, the main picture is that of a decline in second birth rates after 1990 and that rates did not increase again to their pretransition levels.…”
Section: Discussionsupporting
confidence: 87%
“…In their micro data analysis, in fact found a positive relationship between labor market uncertainty/hardship and births between 1994 and 1996. On the other hand, macro level studies found evidence of a positive relationship between fertility and the economy across Russia and post communist Europe UNECE 2000;Cornia and Paniccia 1998;Billingsley 2010). Beyond the need for further research to understand these differential findings, Frejka (2008) has argued that the pathways through which fertility behavior was influenced during the critical transition period remain ambiguous and underspecified in much of the literature.…”
mentioning
confidence: 99%
“…These differences and how they may be related to developments in fertility behaviour and preferences will be further explored in this paper. While contrasting economic trajectories after Armenia's and Moldova's independence, this paper assesses past and current fertility measures from an economic perspective, which could be particularly relevant during a period of tremendous economic restructuring and crisis (Billingsley 2010b;Frejka 2008). A few distinct aims and questions structure this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that regional economic performance can affect fertility trends (for example Adsera 2011, Billingsley 2010. We therefore include a variable for regional GDP per capita, measured in purchasing power standards in 2004 for the NUTS1 regions, because regional wealth differs widely among the regions included in our models (see Table 1 for descriptive statistics).…”
Section: Methodsmentioning
confidence: 99%